Case Report: Acute Post-Streptococcal Glomerulonephritis with Renal Complications and Hemodialysis - Siregar, Christine Bonuria; Indra, Ridha Mutiara; Amiranti, Nugrah Tri (Transpublika Publisher, 2025)
Acute poststreptococcal glomerulonephritis (APSGN) is characterized by infections of the skin (impetigo) or throat (pharyngitis) caused by nephritogenic strains of group A beta-hemolytic Streptococcus. It is more commonly observed in school-aged children, with a mean presentation age between 6 and 8 years. Most studies report a higher prevalence among males, ranging from 54% to 87%. If left untreated, APSGN can lead to chronic kidney failure, hypertension, and recurrent proteinuria. Antibiotic therapy in patients with the primary infection is crucial to prevent the progression of complications. This report aims to describe a current case of APSGN, including its complications, management, and recommended follow-up strategies.